Feedback on feedback: does it work? - Speicher, Oranna; Stollhans, Sascha (Research-publishing.net, 2015)
It is well documented that providing assessment feedback through the medium of screencasts is favourably received by students and encourages deeper engagement with the feedback given by the language teacher (inter alia Abdous & Yoshimura, 2010; Brick & Holmes, 2008; Cann, 2007; Stannard, 2007). In this short paper we will report the results of a case study where students moved from passively receiving feedback to actively entering into a feedback dialogue with their language teachers: screencasts were used not only by the teachers to provide audio and visual feedback to students on their written work, but also by the students themselves to comment in depth on the feedback they had received. Participants in the case study were surveyed at the end of the semester, and we will report on the survey findings as well as discuss the limitations and implications of the case study. The paper will reflect on the potential role of technology in providing feedback, the effectiveness of elicitation feedback in the context of this case study and the students’ perception of the usefulness of creating their own screencasts in response to the feedback they have received.